2016
DOI: 10.1016/j.envint.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Relative effect potency estimates of dioxin-like activity for dioxins, furans, and dioxin-like PCBs in adults based on cytochrome P450 1A1 and 1B1 gene expression in blood

Abstract: Background In the risk assessment of PCDDs, PCDFs, and dioxin-like (DL) PCBs, regulatory authorities support the use of the toxic equivalency factor (TEF)-scheme derived from a heterogeneous data set of the relative effect potency (REPs) estimates. Objectives We sought to determine REPs for dioxin-like compounds (DLCs) using expression of cytochrome P450 (CYP) 1A1 and 1B1 mRNA in human peripheral blood mononuclear cells representing two different pathways. Methods We used a sex and age adjusted regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Of all the isozymes, CYP1 and CYP2 are the major forms involved in PCB metabolism (Hirakawa et al 2018). Because of this, CYP1A1 is often used a biomarker of host exposure to certain persistent organic pollutants (POP) (Foltz et al 2014;Wimmerov a et al 2016). This use as a biomarker is valid in that other studies have previously shown that in the hepatic microsomes of untreated (control) rats, CYP1A1 protein was undetectable (Sidorova et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Of all the isozymes, CYP1 and CYP2 are the major forms involved in PCB metabolism (Hirakawa et al 2018). Because of this, CYP1A1 is often used a biomarker of host exposure to certain persistent organic pollutants (POP) (Foltz et al 2014;Wimmerov a et al 2016). This use as a biomarker is valid in that other studies have previously shown that in the hepatic microsomes of untreated (control) rats, CYP1A1 protein was undetectable (Sidorova et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Wimmerová et al. () studied correlations between relative potencies (REPs) of PCDD/Fs and DL‐PCBs for thyroid impacts (thyroid volume and free T4) and those for CYP1A1 and CYP1B1 gene expression in human peripheral blood mononuclear cells. The authors concluded that while CYP1A1 seems well‐suited for toxicity evaluation of PCDD/F mixtures, CYP1B1 is more apt for that of PCDF/PCB mixtures.…”
Section: Assessmentmentioning
confidence: 99%
“…Brodmann's Area 7 receives a great deal of visual input and sensory information from hands, concurrently TMT and Digit Symbol are both dependent on visual attention and graphomotor skills [35]. Experimentally, TCDD can damage nervous tissue by oxidative stress associated with the AhR-mediated induction of CYP1B1 isoenzyme [36][37][38][39], and the elevation of oxidative stress markers was also found in our patients [17].…”
Section: Discussionmentioning
confidence: 66%